2022
DOI: 10.3389/fimmu.2022.867013
|View full text |Cite
|
Sign up to set email alerts
|

The Past, Present, and Future of Non-Viral CAR T Cells

Abstract: Adoptive transfer of chimeric antigen receptor (CAR) T lymphocytes is a powerful technology that has revolutionized the way we conceive immunotherapy. The impressive clinical results of complete and prolonged response in refractory and relapsed diseases have shifted the landscape of treatment for hematological malignancies, particularly those of lymphoid origin, and opens up new possibilities for the treatment of solid neoplasms. However, the widening use of cell therapy is hampered by the accessibility to vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 193 publications
0
46
0
Order By: Relevance
“…It is generally accepted that the balance between malignancy‐promoting and malignancy‐restraining functions of the TME determines whether a given tumor will progress toward metastasis 2,8 . The recent success of various forms of cancer immunotherapy indicated that the TME exerts powerful anticancer functions 34‐38 . In addition to classical mediators of innate and adaptive anticancer immunity, such as NK or T cells, other factors are endowed with the capacity to exert anticancer resistance, such as antimicrobial peptides 39‐43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that the balance between malignancy‐promoting and malignancy‐restraining functions of the TME determines whether a given tumor will progress toward metastasis 2,8 . The recent success of various forms of cancer immunotherapy indicated that the TME exerts powerful anticancer functions 34‐38 . In addition to classical mediators of innate and adaptive anticancer immunity, such as NK or T cells, other factors are endowed with the capacity to exert anticancer resistance, such as antimicrobial peptides 39‐43 …”
Section: Discussionmentioning
confidence: 99%
“…2,8 The recent success of various forms of cancer immunotherapy indicated that the TME exerts powerful anticancer functions. [34][35][36][37][38] In addition to classical mediators of innate and adaptive anticancer immunity, such as NK or T cells, other factors are endowed with the capacity to exert anticancer resistance, such as antimicrobial peptides. [39][40][41][42][43] In a previous study, we reported that the beta subunit of the mouse (HBB2) and human (HBB) hemoglobin is a lung-derived factor that mediated growth arrest and apoptosis of lung-metastasizing neuroblastoma cells and a variety of other human cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial effort and expense is currently invested in procuring viral vectors for CAR-modification and accordingly, there is significant interest to implement virus-free gene-transfer vectors in CAR T cell manufacturing. 11 12 The Sleeping Beauty (SB) transposon system is virus-free and has been used successfully to accomplish CAR gene-transfer in human T cells in conventional pre-clinical and clinical manufacturing. 5 6 SB transposase and transposon can be vectorized as mRNA and DNA, respectively, and handled with lower risk and in a lower biosafety level environment compared with viral vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Three approved products of CD19-directed CAR T cells are all manufactured by viral gene transfer ( 7 ); however, there have been emerging preclinical and clinical trials using non-viral gene transfer-prepared CAR T cells in the treatment of lymphomas or solid tumors. The advantages of the latter method include lower production cost, well-tolerated toxicities, and higher composition of stem cell memory T cells in the products ( 8 , 9 ). Transposons, as natural non-viral gene delivery vectors, have three types including Sleeping Beauty (SB), Piggy Bac (pb), and Tol2.…”
Section: Introductionmentioning
confidence: 99%
“…The pb system is constituted by the pb transposase and a separate transfer plasmid carrying the desired genetic cargo (CAR construct, for instance). It has a higher transposition activity than SB and a larger cargo size than viral vectors; however, the electroporation process for the delivery of transposon vectors might be toxic to the cells, and the transfection efficiency lower than viral vectors ( 9 ). In a preclinical trial, mesothelin-targeting CAR T cells, prepared by pb, exhibited a rapid and robust killing effect against pancreatic cancer cells; in the xenograft mice model, they significantly suppressed tumor growth, causing minimal lesions in major organs ( 10 ).…”
Section: Introductionmentioning
confidence: 99%